Optimization of sustainable corn–cattle integration in Gorontalo Province using goal programming - Imran Supriyo; Indriani Ria; Hippy Mohammad Zubair (Open Agriculture)
Farmers cannot achieve the optimum profits using an integrated system in corn and cattle farming because they are not utilizing their resources in the best way possible. Therefore, finding better ways to use farm waste as animal food and cow manure as corn plant fertilizer is of utter importance. Goal programming enables a combination of production because it can complete several goals simultaneously. To the best of our knowledge, this type of analysis has not been used in previous livestock crop integration studies. Our study aims to (1) determine the optimal production combination in corn–cattle integration and (2) analyze the optimal allocation of resource use in corn–cattle integration. A total of 66 corn–cattle farmers were interviewed for this study. Data were analyzed through a goal programming model using Linear Interactive and Discrete Optimizer. The results indicate that (1) the optimal production combination with profit targets, production costs, and production risks in corn–cattle integration is met, but the achievement value obtained is still below the target, where the best optimal production combination is 14,693 kg of corn, 18 cows, 3,061 kg of corn waste, and 6,087 kg of compost. (2) In the corn–cattle integration system, the best way to use resources is to increase the supply of medicine, land, and labor by one unit. This is true even if those resources are scarce. The sensitivity interval for the optimal use of production resources in the corn–cattle integration system with the target of profit, cost, and production risk can be increased by 1% from the amount of resources used to infinity and can be reduced by 4–16% of the amount of resources used. To be more food secure, independent, wealthy, and able to support ecosystem sustainability in rural areas, farmers should set up an integrated corn–cattle system with the right mix of output and resource allocation.